Assessing the safety and efficacy of probiotics in improving the gut microbiome of premature infants - Orłowska, Dominika; Olszak, Joanna; Zalewa, Karolina; Bartoszek, Lidia; Kapłan, Wojciech; Starownik , Jakub (Quality in Sport, 2024)
Introduction and Purpose The gut microbiome is crucial to infant health and development. For premature infants, microbiome development differs from full-term babies, posing long-term health risks. Factors such as delivery method, feeding, antibiotic treatment, and neonatal intensive care unit (NICU) environment significantly influence the microbiome of premature infants. Probiotics, especially Bifidobacterium strains, show promise in enhancing health and reducing risks of necrotizing enterocolitis (NEC) and late-onset sepsis (LOS). Material and Methods This review is based on articles from the PubMed database, covering the years 2004-2023, using keywords: gut microbiome, premature infants, probiotic, microbiome development, and neonatal intensive care unit. Results Current research indicates probiotics, particularly Bifidobacterium strains, positively impact the gut microbiome of premature infants, improving immunity and metabolism, and providing protection against NEC and LOS. Multi-strain probiotic preparations combining Bifidobacterium and Lactobacilaceae strains appear promising, but further research is needed to fully understand their effects. Addressing food intolerance (FI) in premature infants is another potential application of microbiome-focused therapies. Conclusions While probiotics show promise in improving the microbiome of preterm infants, comprehensive research on single and multi-strain probiotics and their specific mechanisms of action is needed. Controversies persist regarding the safety, FDA regulation, and selection of specific probiotics and formulations. There is no consensus on the optimal timing for introducing probiotics. Further research is required to optimize probiotic selection and determine the best benefits. Enhanced standardization and oversight are essential to ensure safe and effective use of probiotics in neonatal healthcare.